Lere-koppelmannıń tiykarǵı integrallıq formulası hám onnan kelip shıǵıwshı nátiyje - Qutlımuratov, B.J; Ubbiniyazova, A.B (SCIENCE and SOCIETY, 2022)
The article uses integral formulas with holomorphic kernels. The basic Leray-Koppleman integral formula is studied. The validity of the generalization of the Cauchy-Fantappe formula is proved.
Keywords: differential form; integral formula with holomorphic kernel; vector function; exact form